2019
DOI: 10.1002/ejic.201900759
|View full text |Cite
|
Sign up to set email alerts
|

Mononuclear Hydroxo Carbonato Complexes of Np(V), Np(VI), and U(VI): A Density Functional Study

Abstract: Mononuclear ternary actinide hydroxo carbonato complexes AnO2(OH)y(CO3)zq have been studied computationally for An = Np(V), Np(VI), and U(VI). Density functional calculations were carried out to examine complexes with up to two carbonate and two hydroxide ligands. This study focusses on ternary Np(V) complexes suggested by experiment. Geometry parameters of hydroxo carbonato complexes lie between the corresponding values of hydroxo and carbonato complexes with the same number of anionic ligands. We used calcul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(17 citation statements)
references
References 69 publications
5
12
0
Order By: Relevance
“…A potentiometry measurement determined a somewhat higher value, 23 kJ/mol . We attribute this notable deviation of our results from experiments mainly to shortcomings of the continuum solvation model when comparing species of different charges and sizes. , Similar deviations between experiment and calculations also have been observed for the formation reactions of other complexes modeled including the first solvation shell only. , …”
Section: Resultssupporting
confidence: 46%
See 3 more Smart Citations
“…A potentiometry measurement determined a somewhat higher value, 23 kJ/mol . We attribute this notable deviation of our results from experiments mainly to shortcomings of the continuum solvation model when comparing species of different charges and sizes. , Similar deviations between experiment and calculations also have been observed for the formation reactions of other complexes modeled including the first solvation shell only. , …”
Section: Resultssupporting
confidence: 46%
“…The uranyl cation in water prefers to coordinate five aqua ligands in its first shell, as shown in EXAFS , and NMR studies. Our earlier calculations suggest that the monohydroxo complex [UO 2 (OH)] + coordinates four aqua ligands, leading also to a total CN of 5 in the equatorial plane of uranyl. Therefore, we assume that the equatorial CN of 5 is preserved in the dimeric actinyl aggregate, as also considered previously .…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…The SDD, which treats the 60 core electrons (small core) as the potential to simplify the relativistic effect of heavy atoms, has often been used for transition metals , and UO 2 2+ complexes . The multiplicity ( S ) of the Np­(V)­O 2 + –PDA complex was set to 3. Since no spin contamination was observed, ⟨ S 2 ⟩ in the ground state was equivalent to S ( S + 1), which is identical to the theoretical value. This suggested that the calculation was correctly performed.…”
Section: Experimental Sectionmentioning
confidence: 89%